2003
DOI: 10.1103/physrevlett.91.077203
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Intermetallic Alloys by Ion Irradiation: A Way to Tailor Magnetic Media

Abstract: Combining He ion irradiation and thermal mobility below 600K, we both trigger and control the transformation from chemical disorder to order in thin films of an intermetallic ferromagnet (FePd). Kinetic Monte Carlo simulations show how the initial directional short range order determines order propagation. Magnetic ordering perpendicular to the film plane was achieved, promoting the initially weak magnetic anisotropy to the highest values known for FePd films. This post-growth treatment should find application… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 20 publications
2
74
0
3
Order By: Relevance
“…The thermal annealing of defects occurs on a macroscopic time scale, so that special techniques such as accelerated ticularly important for zero-dimensional objects. For example, only E t = 30 eV transferred to an atom in an isolated fullerene C 60 will raise temperature to T ‫ء‬ ϳ 1 / 3E t / k B / 60 ϳ 2000 K, where k B is the Boltzmann constant, and an additional factor of 0.5 was introduced due to the equipartition theorem.…”
Section: A Production Of Defects In Bulk Targetsmentioning
confidence: 99%
“…The thermal annealing of defects occurs on a macroscopic time scale, so that special techniques such as accelerated ticularly important for zero-dimensional objects. For example, only E t = 30 eV transferred to an atom in an isolated fullerene C 60 will raise temperature to T ‫ء‬ ϳ 1 / 3E t / k B / 60 ϳ 2000 K, where k B is the Boltzmann constant, and an additional factor of 0.5 was introduced due to the equipartition theorem.…”
Section: A Production Of Defects In Bulk Targetsmentioning
confidence: 99%
“…Recently, with the growing use of nanostructured systems in various types of technological devices, the understanding of specificities in energy deposition and damage production by radiation in matter at the nanoscale has become a critical issue. Unique effects of energetic ions on nanoscale systems have already been reported and successfully applied to engineering of materials [10][11][12][13]. Nevertheless, very little has been reported so far on a direct comparison of radiation effects of heavy ions in a material at bulk and spatially confined conditions.…”
mentioning
confidence: 99%
“…Considering Pt/Co(d Co )/Pt pristine films with PMA (d Co < d SRT ), irradiation by He + * corresponding author; e-mail: jo@uwb.edu.pl ions reduces the magnetic interface anisotropy contribution [1,3], the coercivity [1,7] and the Curie temperature [7,8] to finally trigger a SRT [9,10]. From another hand, in chemically disordered FePt films, it has been shown that He + ion irradiation significantly reduces the annealing temperature required for L1 0 alloy ordering [2,11] and reinforces the magnetic anisotropy volume contribution.…”
Section: Introductionmentioning
confidence: 99%